Clinical and Genetic Analysis of a Patient With Coexisting 17a-Hydroxylase/17,20-Lyase Deficiency and Moyamoya Disease - Huang, Jiaming; Zhou, Danli; Dong, Nan; Ding, Chenzhao; Liu, Yan; Li, Fangping (Frontiers in Genetics, 2022)
17a-Hydroxylase/17,20-lyase deficiency (17OHD) is caused by pathogenic mutations in CYP17A1. Female patients present with hypertension, hypokalemia, and sexual infantilism while males present with sex development disorder. Moyamoya disease (MMD) is a chronic cerebrovascular disease that frequently results in intracranial ischemia or hemorrhage. The present study describes a case of 17OHD and MMD in a 27-year-old phenotypically female (46, XY) patient and discusses the clinical features and characteristics of her genetic defect. Clinical, hormonal, radiological, and genetic analyses were performed and blood samples were collected for whole-exome sequencing (WES). The results of the WES revealed a homozygous intronic mutation (c.297+2T>C) in CYP17A1, which led to combined 17a-hydroxylase/17,20-lyase deficiency, as well as novel variants in PCNT and CNOT3 that might lead to MMD. To our knowledge, this study is the first to describe 17OHD accompanied by MMD. While several cases have previously described patients with 17OHD with histories of cerebral hemorrhage or cerebral ischemia, a correlation in genetic levels between 17OHD and MMD was not found. The risk of cerebrovascular accidents should be considered in patients with 17OHD and hypertension. Cerebrovascular examination in patients with 17OHD may be beneficial for the prevention of life-threatening intracranial vascular disease.